Anaerobic digestion of sugarcane bagasse for biogas production and digestate valorization. (May 2022) - Agarwal, Nitin Kumar; Kumar, Madan; Ghosh, Pooja; Kumar, Smita S.; Singh, Lakhveer; Vijay, Virendra Kumar; Kumar, Vivek
Abstract: Sugarcane bagasse is an abundantly available agricultural waste having high potential that is still underutilized and mostly burnt as fuel. There are various processes available for bagasse utilization in improved ways and one such process is anaerobic digestion (AD) of bagasse for biogas production. The complex structure of biomass is recalcitrant to degradation and is a major hindrance for the anaerobic digestion, so different pretreatment methods are applied to deconstruct the bagasse for microbial digestion. In this review, different processes developed for the pretreatment of bagasse and their effect on biogas production have been extensively covered. Moreover, combination of pretreatment methods, co-digestion of bagasse with other waste (nitrogen rich or easily digestible) for enhanced biogas production and biomethane generation along with other value-added products has also been reviewed. The digestate contains a significant amount of organics with partial recovery of energy and products and is generated in huge amount that further creates disposal problem. Therefore, integration of digestate valorization with AD through gasification, pyrolysis, hydrothermal carbonization and use of microalgae for maximum recovery of energy and value-added products have also been evaluated. Thus, this review highlights major emerging area of research for improvement in bagasse based processes for enhanced biogas production along with digestate valorization to make the overall process economical and sustainable. Graphical abstract: Image 1 Highlights: Pretreatment processes for bagasse based biogas generation are extensively discussed. Emerging strategies adopted for enhanced biogas generation from surgarcane bagasse. Promising research on bagasse to biomenthane along with other value-added products explored. Recent researches on digestate valorization routes are comprehensively discussed.